Strong hypoxia reduces leptin synthesis in purified primary human trophoblasts - Nuesken, E.; Herrmann, Y.; Wohlfarth, M.; Goecke, Tamme W.; Appel, S.; Schneider, Holm; Doetsch, J.; Nuesken, K. D. (Placenta, 2015)
Introduction Oxygen availability severely affects placental function. During placental hypoxia, stabilization of hypoxia inducible factors (HIFs) affects transcription, and leptin gene expression concomitantly increases in vivo and in vitro. However, a causal relationship is uncertain.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Hypoxia; Leptin/leptin receptor; Placenta; Trophoblast